2014
DOI: 10.5812/jjm.9930
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus in Chronic Cervicitis, Cervical Adenocarcinoma, Intraepithelial Neoplasia and Squamus Cell Carcinoma

Abstract: Background:Cervical cancer is the second most common cancer in women worldwide. Recent studies show that human papillomavirus (HPV) DNA is present in all cervical carcinomas and in some cervicitis cases, with some geographical variation in viral subtypes. Therefore determination of the presence of HPV in the general population of each region can help reveal the role of these viruses in tumors.Objectives:This study aimed to estimate the frequency of infection with HPV in cervicitis, cervical adenocarcinoma, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…[ 6 ] Another study found that 78 of 79 patients with chronic cervicitis tested positive for HPV. [ 8 ] In accordance with these studies, we found that before treatment, approximately 80% of patients were diagnosed with cervicitis and vaginitis, suggesting that HPV infection may cause local mucosal damage and contribute to cervicitis and vaginitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…[ 6 ] Another study found that 78 of 79 patients with chronic cervicitis tested positive for HPV. [ 8 ] In accordance with these studies, we found that before treatment, approximately 80% of patients were diagnosed with cervicitis and vaginitis, suggesting that HPV infection may cause local mucosal damage and contribute to cervicitis and vaginitis.…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that the rate of HPV infection in chronic cervicitis cases was 98.7% (78/79). [ 8 ] In addition, bacterial infections appear to facilitate persistent HPV infections. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…3 Most of the cervical carcinomas are associated with human papilloma-virus (HPV) as rate of HPV and HIV infection in chronic cervicitis cases is much higher as observed by Ealhe, Atsuki et al in his study of CSC noticed that interactions between MSCs and tumor cells in tumor tissues could become a new cancer therapy target. [7][8][9][10] Autologus stem cell therapy can emerge as a potential treatment strategy for chronic cervicitis, with promising result for inflamed and damaged cervical tissue. As treatment with AASCs showed reversal of chronic inflammatory changes with healing of erosions, improved symptoms and better cervical health with improved quality of life and well-being, in long term prevention from Ca Cervix is expected.…”
Section: Discussionmentioning
confidence: 99%
“…We have also observed a low frequency of HPV infection (HPV [4.6%]; HPV16 [2.3%]; HPV18 [0%]) and no coexistence of the investigated pathogens in the cervicitis patients. The prevalence of HPV in cervicitis has shown an inconsistent pattern world-over, as observed in Korea (HPV [56.8%]; HPV16 [10.6%]; HPV18 [6.8%)]) [51], Iran (HPV [98.7%]) [52] and Greece (HPV [36%]; HPV16 [12%]; HPV18 [15%]) [53]. Although our data suggest no significant involvement of HPV in cervicitis; however, women when presented with cervicitis, should also be investigated for the presence of HPV, as the presence of HPV in cervicitis may serve as a compounding factor towards cervical carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%